2015
DOI: 10.1038/nnano.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

Polarization charge as a reconfigurable quasi-dopant in ferroelectric thin films

Abstract: Impurity elements used as dopants are essential to semiconductor technology for controlling the concentration of charge carriers. Their location in the semiconductor crystal is determined during the fabrication process and remains fixed. However, another possibility exists whereby the concentration of charge carriers is modified using polarization charge as a quasi-dopant, which implies the possibility to write, displace, erase and re-create channels having a metallic-type conductivity inside a wide-bandgap se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
193
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(199 citation statements)
references
References 27 publications
6
193
0
Order By: Relevance
“…McQuaid, private communication), (Bi 0.9 La 0.1 )FeO 3 (ref. 12)) and initial concerns that currents were not necessarily genuinely associated with enhanced conductivity (instead arising from undetected domain wall movement for example) have now been firmly allayed. Since the domains themselves are comparatively insulating, domain walls represent isolated conducting channels, which confine currents into narrow sheets.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…McQuaid, private communication), (Bi 0.9 La 0.1 )FeO 3 (ref. 12)) and initial concerns that currents were not necessarily genuinely associated with enhanced conductivity (instead arising from undetected domain wall movement for example) have now been firmly allayed. Since the domains themselves are comparatively insulating, domain walls represent isolated conducting channels, which confine currents into narrow sheets.…”
mentioning
confidence: 97%
“…There is an expectation that domain walls should have electronic band-structures that differ from domains1920, but there is also clear evidence that stress and/or electrostatic interactions with charged point defects can be important589101112212223. Key carrier information is still lacking, as basic transport characterization studies within the walls have been limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to create, displace, and erase the charged domain walls (CDW) by the application of the external electric field, which implies the possibility to build real-time reconfigurable devices. Currently, the influence of CDW on the conductivity [1], dielectric permittivity [2], and piezoelectric coefficient [3] of ferroelectrics has been revealed. It has been shown that the bulk properties can be effectively modified by formation of the high density of the domain walls [3].…”
Section: Introductionmentioning
confidence: 99%
“…While it is well known that properties of the ferroelectrics such as piezoelectric effect and permittivity are substantially enhanced by mobile and stationary domain walls2345, the ferroelectric domain walls themselves were found recently to possess unique properties that differ thoroughly from the bulk domains, for example, electronic conductivity678 and photovoltaic effect9. These results raise much interest101112 in further exploration of the properties of domain walls and their internal structures.…”
mentioning
confidence: 99%